2008
DOI: 10.1088/0953-8984/20/20/205108
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of water/ice formation in SBA-15 silicas: III. The triplet profile for 86 Å pore diameter

Abstract: Abstract. The diffraction results for the formation of ice in 86Å diameter pores of a SBA-15 silica sample are analysed to provide information on the characteristics of the ice created in the pores. The asymmetric triplet at ∼1.7Å −1 , which involves several overlapping peaks, is particularly relevant to the different ice phases and contains a number of components that can be individually identified. The use of a set of three peaks with an asymmetric profile to represent the possibility of facetted growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
7
35
0
Order By: Relevance
“…However, current on-going studies 39,39 with carbon nanotubes of ∼30Å reveal that the water properties are found to be quite distinctive and considerably different from the results obtained in this current study. Some features are similar to those already seen in other work on templated mesoporous silicas 23,24,25,26 . However, some new results have also been obtained, particularly in relation to the use of the modified sample with a hydrophobic interface:-…”
Section: Summary and Futher Worksupporting
confidence: 85%
See 1 more Smart Citation
“…However, current on-going studies 39,39 with carbon nanotubes of ∼30Å reveal that the water properties are found to be quite distinctive and considerably different from the results obtained in this current study. Some features are similar to those already seen in other work on templated mesoporous silicas 23,24,25,26 . However, some new results have also been obtained, particularly in relation to the use of the modified sample with a hydrophobic interface:-…”
Section: Summary and Futher Worksupporting
confidence: 85%
“…These results suggest a two-stage process in which the initial nucleation event causes a fraction of the water to crystallise as hexagonal ice but the subsequent growth is predominantly in the form of cubic ice. This feature is similar to that observed in the detailed studies of ice nucleation in SBA-15 silica samples with a pore size of 86Å 23,24,25 and is discussed more fully in Section 4.…”
Section: Non-modified Silicasupporting
confidence: 83%
“…From our diffraction studies we now find that significant amounts of amorphous phase are unlikely to exist in contact with "ice I c "; earlier evidence for amorphous relics in "ice I c ", based on a simplified analysis of low-resolution diffraction data (16,39,43), should be reconsidered in the light of an appropriate model for stacking disorder and with higher-resolution data, in line with the conclusions of Mitlin and Leung (53). The situation may, however, be different for solutes at high concentration, which impede or even prevent any water crystallization at temperatures even far below the melting point (55).…”
Section: Discussionmentioning
confidence: 48%
“…For a satisfactory description, interactions up to the next-nearest layer had to be introduced, leading to four independent parameters α, β, γ, and δ corresponding to an interaction range s = 4 (SI Text). Using this model, a very satisfactory agreement between experimental observation and the model was obtained in all investigated cases; the introduction of amorphous components (16,39) was not necessary to obtain a good fit. In particular, at lower and intermediate temperatures the complex stacking-disordered nature of "ice I c " cannot be fully captured in the model set up by Malkin et al (8) and computed with DIFFaX (40).…”
Section: Resultsmentioning
confidence: 60%
“…A system consisting of water/ice in a cylindrical pore templated SBA-15 porous silica [77] has been probed using neutron diffraction, neutron diffraction cryoporometry, NMR transverse relaxation and NMR cryoporometry techniques [2,83,20,78,87,88].…”
Section: Water/ice At a Silica Interfacementioning
confidence: 99%